Travelogues and Islamic Historical Sources up to the Eighth Hijri Century A Study of the Myths and Miracles Associated with the Mushaf of Caliph Uthman ibn Affan. - Salam Nasser Wali AL-Adami, Dr. (lark, 2026)
This study examines and analyzes the phenomenon of miraculous narratives and miracles linked to the Mushafs, specifically the Mushaf of Caliph Uthman ibn Affan, as recorded in Islamic historical sources and the writings of Muslim travelers up to the end of the Eighth Hijri Century. The study aims to explore the symbolic structure and the religious and political functions of these narratives within the Islamic imagination, analyzing the contexts in which they arose and the objectives they served within the development of Islamic thought and the formation of sectarian identities. The research focuses on analyzing various historical texts that recount miracles attributed by some historians to the Mushaf that was in Uthman’s possession at the time of his assassination, such as the Mushaf speaking, being stained with his blood on a specific verse, not burning, or remaining a silent witness to the great discord. The study concludes that the Mushaf, through these narratives, transformed from a revealed religious text into a mythological symbol imbued with meanings that transcend its original function, becoming a witness to sanctity, political division, or the victimization of an individual or group. The study further demonstrated that the utilization of mythology in the portrayal of the Mushafs, especially the Mushaf of Uthman, constituted a crucial instrument in the construction of legitimacy discourse and the reconfiguration of the memory of the Fitna within the Islamic collective consciousness.